RAW WATER RELIABILITY STUDY OF THE KRUENG ACEH RIVER FOR DEVELOPING OF BANDA ACEH CITY PIPED DRINKING WATER SERVICE SYSTEM - Mirza Aulia, M.
The increase in population causes an increase in the need for clean water. The provision of clean water in Banda Aceh City by PDAM Tirta Daroy with a capacity of 730 l/s with raw water sources coming from the Krueng Aceh River, Krueng Aceh Watershed. In the Piped Drinking Water Service System Plan of Banda Aceh City 2015 it is planned to increase production capacity by 1916 l/s in 2035. So, a reliable source of raw water is needed to meet the increase in production capacity of 1186 l/s. The reliability of raw water sources can be seen by statistical analysis on successive dry minimum discharge data of 1, 2, 7, 15, and 30 days duration by carrying out a theoretical distribution fit test with a goodness of fit test. The types of distribution used to analyze dry extreme discharge are the Gumbel, Log-Normal, and Log-Pearson III distributions (Linsley, 1969 and Soewarno, 1995). From the results of the analysis, the Krueng Aceh river can meet the needs of raw water sources until 2035 according to Piped Drinking Water Service System Plan of Banda Aceh City 2015 with the mainstay discharge is QR20-1 = 4.89 m3 /s. Planning to increase production capacity is carried out with the construction of WTP in 2 stages, 800 l/s and 400 l/s. The selection of WTP units uses the surface water SPAM concept and the alternative selection method for treatment units uses Simple Additive Weighting (SAW) with the selected treatment consisting of presedimentation units of coagulation, flocculation, sedimentation, filtration, disinfection, and reservoir.